Estimation of yield loss in soybean triggered by Spodoptera litura: Estimation of yield loss in soybean triggered by Spodoptera litura - B SUNDAR,; NANDA KHANDWE,; M SURYA PRAKASH, (Journal of Oilseeds Research, 2020)
Pest infestation has been identified as the major biotic factor limiting soybean yield worldwide. The currentscenario of management mainly focuses on insecticides with a quick knockdown effect, not with host plant resistance techniques. The present work is for comparing both chemical and plant resistance. Fifty soybean genotypes with four replications (2 treated + 2 untreated) screened against Spodoptera litura infestation. Among them eleven varieties were resistant and high yielding (R-HY), seventeen were resistant and low yielding (R-LY) and twenty two varieties were susceptible and low yielding (S-LY). The grain yield range from 475.0 to 2375.0 kg/ha and 450.0 to 2263.0 kg/ha, in treated and untreated varieties, respectively. The grain yield loss ranged from 0.67 to 17.71 per cent in different varieties.